REDESIGNING ASSEMBLY LINE BY APPLYING RANKED POSITIONAL WEIGHT AT HEAVY-INDUSTRIAL FACILITY - Hery Hamdi Azwir; Adji Fadjriawan Nugraha (Spektrum Industri, 2020)
To meet customer demand, the company was faced with insufficient capacity problems caused by low efficiency and congestion on the assembly line. Recent data shows that there is an imbalance in the work process time between workstations. This study aims to solve these problems to achieve the desired capacity. The research begins by observing the operating time and collecting other data on the assembly line then analyzed and developed as a solution to these problems. The analysis results show that the assembly line has low line efficiency and the impact on the output target is not as expected. From the time observations made on the assembly line, it can be seen that the current line is inefficient and there is a bottleneck at some workstations. Ranked Positional Weight (RPW) was chosen as a line balancing method to solve the problem. RPW generates new work arrangements for each workstation that has relatively the same uptime. The results of the RPW method showed a significant increase in line efficiency, namely 75.03%, the smoothness index increased by 90.79%, and the balance delay was reduced by 90.52%. After the solution is obtained, a new layout is created to be used as a guide for rearranging the assembly line.